Exploring Brand Activism Through Psychometric and Demographic Lenses in Emerging Markets - Emaridial Ulza (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the evolving global marketplace, brands are increasingly evaluated based on their social and environmental contributions, particularly in emerging economies like Indonesia. This study explores how Indonesian consumers perceive brand activism, philanthropy, emotional connection, authenticity, purchase intention, and brand social activity using Rasch Model Analysis. Based on responses from 617 participants, the Wright maps reveal nuanced patterns in item-person alignment across six brand-related constructs. While most respondents demonstrate high support for brand activism and philanthropy, item-level analysis indicates cautious endorsement, reflecting skepticism about the sincerity of brand initiatives. Emotional connection and perceived authenticity emerged as key mediators in driving purchase intention, yet their depth varies by item. Differential Item Functioning analysis highlights significant perception differences based on age, occupation, gender, education, and region. Older participants and those outside the urban Jabodetabek region show stronger reactions to boycott-related messaging, while younger and student respondents report higher emotional brand identification. The findings underscore the importance of culturally resonant and demographically sensitive branding strategies, offering empirical insights into how social initiatives influence consumer behavior in emerging markets.